2012
DOI: 10.3109/09540261.2012.704873
|View full text |Cite
|
Sign up to set email alerts
|

Early intervention in schizophrenia in developing countries: Focus on duration of untreated psychosis and remission as a treatment goal

Abstract: Early intervention services are based on the premise that untreated psychosis may have a deleterious effect on outcome, particularly in the early years of illness. The majority of the studies on duration of untreated psychosis have been conducted in developed countries; therefore this review focuses on publications from developing countries. We also review studies from developing countries that have been published following the Remission in Schizophrenia Working Group criteria. The duration of untreated psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 33 publications
1
18
1
Order By: Relevance
“…A previous review suggested that the correlation between DUP and outcome in developing countries was somewhat contradictory as the DUP tended to be longer but remission rates were higher, despite some correlation between long DUP and poor outcome. 33 Our meta-analysis gives only limited information on differences between countries based on the level of income. There was no study from a low-income country and only a few (from none to four) studies from countries with lower- or higher-middle level of income in each of the outcome categories.…”
Section: Discussionmentioning
confidence: 99%
“…A previous review suggested that the correlation between DUP and outcome in developing countries was somewhat contradictory as the DUP tended to be longer but remission rates were higher, despite some correlation between long DUP and poor outcome. 33 Our meta-analysis gives only limited information on differences between countries based on the level of income. There was no study from a low-income country and only a few (from none to four) studies from countries with lower- or higher-middle level of income in each of the outcome categories.…”
Section: Discussionmentioning
confidence: 99%
“…Both findings have public health significance. Long durations of untreated psychosis have been reported in Sub-Saharan Africa compared to high income countries and have been associated with poorer outcomes [54][55][56]. Late onset of psychotic illnesses is often associated with a less severe course and better outcomes [57].…”
Section: Age Of Initial Presentation With a First Episode Of Psychosismentioning
confidence: 99%
“…Basic symptoms consist of subclinical subtle disturbances in stress tolerance, affect, thinking, speech, drive, perception and motor action [ 8 , 9 ] appearing before the appearance of APS or BLIPS, thus allowing for detection of at risk patients at an earlier stage. There is accumulating evidence that the onset of psychosis can be prevented by intervening in this risk phase [ 10 12 ] and treatment in the early stages of schizophrenia is critical to the progression of the disease [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%